Geochemistry of the Archean Kam group, yellowknife Greenstone Belt, Slave Province, Canada - Cousens, B. (Brian) (The Journal of Geology, 2000)
The geochemistry and isotope systematics of Archean greenstone belts provide important constraints on the origin of the volcanic rocks and tectonic models for the evolution of Archean cratons. The Kam Group is a ~10-km-thick pile of submarine, tholeiitic mafic, and subordinate felsic volcanic rocks erupted between 2712 and 2701 Ma that forms the bulk of the Yellowknife greenstone belt in the dominantly granite-metasedimentary Slave Province. Mafic rocks range from Normal-mi